Duplication/triplication mosaicism of EBF3 and expansion of the EBF3 neurodevelopmental disorder phenotype. (March 2022) - Ignatius, Erika; Puosi, Riina; Palomäki, Maarit; Forsbom, Noora; Pohjanpelto, Max; Alitalo, Tiina; Anttonen, Anna-Kaisa; Avela, Kristiina; Haataja, Leena; Carroll, Christopher J.; Lönnqvist, Tuula; Isohanni, Pirjo
Abstract: Deleterious variants in the transcription factor early B-cell factor 3 ( EBF3 ) are known to cause a neurodevelopmental disorder (EBF3-NDD). We report eleven individuals with EBF3 variants, including an individual with a duplication/triplication mosaicism of a region encompassing EBF3 and a phenotype consistent with EBF3-NDD, which may reflect the importance of EBF3 gene-dosage for neurodevelopment. The phenotype of individuals in this cohort was quite mild compared to the core phenotype of previously described individuals. Although ataxia tended to wane with age, we show that cognitive difficulties may increase, and we recommend that individuals with EBF3-NDD have systematic neuropsychological follow-up. Highlights: Individuals with EBF3 variants may have mild phenotypes without intellectual disability. Copy number gain of EBF3 is associated with a neurodevelopmental phenotype. Cognitive difficulties in individuals with EBF3 variants may increase with age. EBF3 variants may be associated with cortical malformations.